Emerging drugs for eosinophilic esophagitis. (3rd April 2018) - Pesek, Robert D.; Gupta, Sandeep K.
ABSTRACT: Introduction : Eosinophilic esophagitis (EoE) is rare but incidence and prevalence is increasing. EoE is characterized by eosinophilic inflammation of the esophagus causing gastrointestinal symptoms such as abdominal pain, vomiting, reflux, dysphagia, and food impactions. If untreated, remodeling and fibrosis of the esophagus can occur and stricture formation may result. Current treatment options are limited to food-restriction diets or medications including proton pump inhibitors (PPIs) or swallowed corticosteroids. Significant progress has been made in understanding the underlying mechanisms of EoE allowing for development of drugs that target specific points in EoE pathways. Investigation of these drugs is early with few controlled studies, but many show promise as future treatments. Areas covered : This review will provide an up to date discussion of current therapies and investigational drugs for EoE. Articles used in this review were retrieved from PubMed. Ongoing or completed clinical trials were obtained through clinicaltrials.gov and review of the PharmaProjects database. Expert Opinion : Multiple therapeutic targets have been identified and several have shown efficacy. Work is needed to define appropriate trial outcome measures. Collaboration between government agencies, patient advocacy groups, and investigator-led consortia is critical for completing new clinical trials which should pave the way for new therapies in clinical practice.